Conjugate-Symplecticity of Linear Multistep Methods (Journal of Computational Mathematics, 2018)
For the numerical treatment of Hamiltonian differential equations, symplectic integrators are the most suitable choice, and methods that are conjugate to a symplectic integrator share the same good long-time behavior. This note characterizes linear multistep methods whose underlying one-step method is conjugate to a symplectic integrator. The boundedness of parasitic solution components is not addressed.
Keywords: Linear multistep method; Underlying one-step method; Conjugate-symplecticity; Symmetry.